Critical evaluation of touch DNA recovery methods for forensic purposes. Issue 1 (December 2019) - Hartless, Sophie; Walton-Williams, Laura; Williams, Graham
Abstract: Over the past decade there has been a significant increase in the number of submissions of 'touch DNA' evidence to forensic laboratories. Previous research has indicated that analysis of these samples produces low success rates. Published research, as well as case work review by forensic practitioners, has also indicated more consideration of how to improve the evidential value of 'touch DNA' samples is needed. Therefore, this research aims to critically evaluate low level DNA recovery methods in order to maximise efficiency for forensic identification purposes. Typical evidential items, such as plastic handled screwdrivers, aluminium cans, drinking glasses and wooden handles, were handled in a mock-operational trial. The deposited DNA was recovered from these items using a range of swabbing materials including cotton, polyester and foam. These samples then underwent quantitative PCR analysis and were profiled using AmpFLSTR™ NGM SElect™. The DNA quantity and quality were compared and a statistically significant differences were found to be present between recovery methods with the foam swab recovering more donor alleles overall.